Dual Emission of a Free‐Base 5‐Oxaporphyrinium Cation from its cis‐ and trans‐NH Tautomers. (11th December 2020) - Takiguchi, Asahi; Kang, Seongsoo; Fukui, Norihito; Kim, Dongho; Shinokubo, Hiroshi
Abstract: Replacement of the meso methine carbon atoms of porphyrins with heteroatoms is a powerful strategy for tuning their optical and electronic properties. In particular, 5‐oxaporphyrin is an attractive target due to its importance as an intermediate in heme catabolism. In this work, we describe the synthesis and properties of a free‐base 5‐oxaporphyrinium cation, which was prepared by the ring‐closure of a bilindione with trifluoromethanesulfonic anhydride. This free‐base 5‐oxaporphyrinium cation exhibits dual fluorescence originating from its unique NH tautomerism. In contrast to normal porphyrins, the cis form of the 5‐oxaporphyrinium cation is more stable than the trans form due to the effective delocalization of its positive charge. We thus demonstrate here that meso‐modified heteroporphyrins enable the manipulation of NH tautomerism in porphyrinic macrocycles. Abstract : Treatment of a bilindione with trifluoromethanesulfonic anhydride afforded a free‐base 5‐oxaporphyrinium cation. This compound exhibits unusual NH tautomerism, wherein the cis form is more stable than the trans form due to effective charge delocalization, which manifests in dual emission.